Easy and Rapid Purification of Highly Active Nisin. (18th September 2011) - Abts, André; Mavaro, Antonino; Stindt, Jan; Bakkes, Patrick J.; Metzger, Sabine; Driessen, Arnold J. M.; Smits, Sander H. J.; Schmitt, Lutz
Abstract : Nisin is an antimicrobial peptide produced and secreted by several L. lactis strains and is specifically active against Gram-positive bacteria. In previous studies, nisin was purified via cation exchange chromatography at low pH employing a single-step elution using 1 M NaCl. Here, we describe an optimized purification protocol using a five-step NaCl elution to remove contaminants. The obtained nisin is devoid of impurities and shows high bactericidal activity against the nisin-sensitive L. lactis strain NZ9000. Purified nisin exhibits an IC50 of ~3 nM, which is a tenfold improvement as compared to nisin obtained via the one-step elution procedure.